Optimization of Wood Waste Utilization for Sustainable Material Processing in the Furniture Industry - Afifah, Anshah Silmi; Nugroho, Alfani Risman; Nurmadina, Nurmadina; Fitriyanto, Taufik Ramadhan; Juwitasari, Dhian (Journal of Engineering Science and Technology Management (JES-TM), 2025)
This study aims to identify and quantify wood waste produced during the machining of solid wood components using kiln dried Durio zibethinus boards. A descriptive quantitative approach was employed to measure the volume and weight of waste generated at each production stage, including ripping, crosscutting, planing, and thicknessing. Sampling was conducted using a precision digital scale to collect and compare the actual and theoretical waste. The results indicate that only 43% of the raw material volume was utilized in finished components, while 57% was lost as waste, primarily in the form of sawdust, shavings, and offcuts. The thicknesser contributed the largest proportion of waste (58%), followed by the ripsaw (21%), single planer (20%), and jumpsaw (1%). These findings highlight the need for improved raw material selection, more efficient cutting list design, enhanced nesting strategies, and better machine calibration. Implementing these practices can reduce wood waste, improve material efficiency, and minimize occupational exposure to wood dust in furniture manufacturing